Native bacteria from the caatinga biome mitigate the effects of drought on melon (Cucumis melo L.) - Dias, Kayo César Fernandes Pereira; da Silva Souza, Igor Juliano; Costa Barros, Yasmin; Pereira da Silva, Edilania; Leite, Jakson; Freire Araújo Feitoza, Adriane; Feitoza de Jesus Santos, Adailson (Comunicata Scientiae, 2023)
Plant growth-promoting bacteria (PGPB) from drylands are promising biological resources to mitigate the negative effects induced by water deficit. The aim of this study was to evaluate the effects of bacteria native from the Caatinga biome on the initial growth of melon plants subjected to water deficit. Nine bacteria (M1.1, T11.2, PH5.2, T11.1, T2.1, T1.1, M7.1, XX6.9 and XX6.6) isolated from Caatinga soils were tested in two varieties of melons (Cantaloupe and Yellow) cultivated under two water availability scenarios (50% irrigation and 100% irrigation of the crop evapotranspiration - ETc). In the control treatment, no inoculation was performed. The effects of the treatments on shoot length (SL), shoot dry mass (SDM), root length (RL) and root dry mass (RDM) were evaluated. In the scenario without water deficit (100% ETc replacement), the isolates PH5.2, T2.2, M7.1, XX6.9 promoted (p<0.05) the root and shoot biomasses in the Cantaloupe variety, while in the Yellow variety, growth promotion was sporadic, with three isolates (M1.1, M7.1 and XX6.9) promoting at least one parameter evaluated. In the scenario with a water deficit (50% ETc replacement), isolates T1.1 and XX6.9 promoted the total biomasses (SDM and RDM) of the Cantaloupe and Yellow varieties, respectively. All isolates stimulated RL in the Cantaloupe variety. Bacteria isolated from the Caatinga promote growth and reduce the effects of water deficit in melon and thus are potential inoculants to enhance production in the early stages of melon cultivation in semiarid regions.